Criminal Responsibility of Medical Personnel After the Enactment of Law No. 17 of 2023: Analysis of Article 438 concerning Rejection of Emergency Patients - Sadrina Hasan, Durra; Aspan, Henry (International Conference Epicentrum of Economic Global Framework, 2025)
This study analyzes the criminal liability of medical personnel following the enactment of Law No. 17 of 2023, specifically focusing on Article 438 concerning the refusal of emergency patients. Utilizing a normative legal research method, this article examines the legal framework, relevant doctrines, and jurisprudential developments. The findings indicate that Law No. 17 of 2023 strengthens the legal protection for emergency patients by imposing stricter criminal sanctions on healthcare facilities and personnel who fail to provide initial assistance or refuse emergency care. Article 438 introduces a tiered criminal liability, with more severe penalties if the refusal leads to disability or death. This shift emphasizes the ultimum remedium principle, ensuring accountability and deterring negligence in emergency medical services. The study concludes that the new law aims to uphold patient rights and enhance the social function of healthcare providers, necessitating robust internal protocols and ethical adherence within healthcare facilities.